Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Modeling nearshore total phosphorus in Lake Michigan using linked hydrodynamic and water quality models - James J. Pauer; Mark D. Rowe; Wilson Melendez; Thomas P. Hollenhorst; Lisa L. Lowe; Peter J. Alsip; Dale M. Robertson; Steven A. Pothoven (Ecological Modelling, 2024)

Wind and small mammals are complementary fungal dispersers - Benjamin W. Borgmann‐Winter; Ryan B. Stephens; Mark A. Anthony; Serita D. Frey; Anthony W. D'Amato; Rebecca J. Rowe (Ecology, 2023)
Following a disturbance, dispersal shapes community composition as well as ecosystem structure and function. For fungi, dispersal is often wind or mammal facilitated, but it is unclear whether these pathways are complementary or redundant in the taxa they disperse and the ecosystem functions they provide. Here, we compare the diversity and morphology of fungi dispersed by wind and three rodent species in recently harvested forests using a combination of microscopy and Illumina sequencing. We demonstrate that fungal communities dispersed by wind and small mammals differ in richness and composition. Most wind‐dispersed fungi are wood saprotrophs, litter saprotrophs, and plant pathogens, whereas fungi dispersed in mammal scat are primarily mycorrhizal, soil saprotrophs, and unspecified saprotrophs. We note substantial dispersal of truffles and agaricoid mushrooms by small mammals, and dispersal of agaricoid mushrooms, crusts, and polypores by wind. In addition, we find mammal‐dispersed spores are larger than wind‐dispersed spores. Our findings suggest that wind‐ and small‐mammal‐facilitated dispersal are complementary processes and highlight the role of small mammals in dispersing mycorrhizal fungi, particularly following disturbances such as timber harvest.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Predicting larval alewife transport in Lake Michigan using hydrodynamic and Lagrangian particle dispersion models - Mark D. Rowe; Sara E. Prendergast; Karen M. Alofs; David B. Bunnell; Edward S. Rutherford; Eric J. Anderson (Limnology and Oceanography, 2022)
Several species of fish in large lakes and marine environments have a pelagic larval stage, and are subject to variable transport that can ultimately regulate survival and recruitment success. Alewife, Alosa pseudoharengus , are subject to transport by complex coastal currents during their pelagic larval stage (~ 30 d). We assessed backward‐trajectory simulations, consisting of a Lagrangian particle dispersion model linked to the Finite Volume Community Ocean Model, to estimate likely hatch locations of aged larval alewife collected from locations on both the eastern and western sides of Lake Michigan during July 2015. We used four deployments of three satellite‐tracked drifter buoys in coastal waters to assess model skill in estimating the origin of a drifter from its final location. We found that the trajectories of drifters varied greatly, depending on wind events and associated coastal transport processes, including upwelling/downwelling and coastal jet currents. In 2 of 12 cases, the backward trajectory simulations failed to predict the drifter origin, associated with transport of 170 km in a narrow coastal jet current. In the remaining 10 cases, the known drifter origin was within 3.5 km of the spatial patch of predicted possible origins for a scenario of horizontal diffusivity (188 m 2 s −1 ) consistent with the offshore model grid resolution. Modeled backward trajectories estimated that alewife originated from the same side of the lake where they were collected, within ~ 100 km of the collection site. Our paper demonstrates the utility of hydrodynamic models to estimate a region of origin for aged larval fish.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The use of Bayesian methodology in the development and validation of a tiered assessment approach towards prediction of rat acute oral toxicity - James W. Firman; Mark T. D. Cronin; Philip H. Rowe; Elizaveta Semenova; John E. Doe (Archives of Toxicology, 2022)
There exists consensus that the traditional means by which safety of chemicals is assessed—namely through reliance upon apical outcomes obtained following in vivo testing—is increasingly unfit for purpose. Whilst efforts in development of suitable alternatives continue, few have achieved levels of robustness required for regulatory acceptance. An array of “new approach methodologies” (NAM) for determining toxic effect, spanning in vitro and in silico spheres, have by now emerged. It has been suggested, intuitively, that combining data obtained from across these sources might serve to enhance overall confidence in derived judgment. This concept may be formalised in the “tiered assessment” approach, whereby evidence gathered through a sequential NAM testing strategy is exploited so to infer the properties of a compound of interest. Our intention has been to provide an illustration of how such a scheme might be developed and applied within a practical setting—adopting for this purpose the endpoint of rat acute oral lethality. Bayesian statistical inference is drawn upon to enable quantification of degree of confidence that a substance might ultimately belong to one of five LD50-associated toxicity categories. Informing this is evidence acquired both from existing in silico and in vitro resources, alongside a purposely-constructed random forest model and structural alert set. Results indicate that the combination of in silico methodologies provides moderately conservative estimations of hazard, conducive for application in safety assessment, and for which levels of certainty are defined. Accordingly, scope for potential extension of approach to further toxicological endpoints is demonstrated.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Lake morphometry determines Dreissena invasion dynamics - Alexander Y. Karatayev; Vadim A. Karatayev; Lyubov E. Burlakova; Knut Mehler; Mark D. Rowe; Ashley K. Elgin; Thomas F. Nalepa (Biological Invasions, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Modeling the interactive effects of nutrient loads, meteorology, and invasive mussels on suitable habitat for Bighead and Silver Carp in Lake Michigan - Peter J. Alsip; Hongyan Zhang; Mark D. Rowe; Edward Rutherford; Doran M. Mason; Catherine Riseng; Zhenming Su (Biological Invasions, 2020)
Anthropogenic stressors that affect ecological processes in the Laurentian Great Lakes can impact their susceptibility to bioinvasions. Bighead Hypophthalmichthys nobilis and Silver Carp H. molitrix , collectively ‘bigheaded carps’ (BHC), are planktivorous fishes threatening to invade Lake Michigan. While previous studies indicate the lake contains habitat suitable for BHC growth, there is a need to understand how anthropogenic-driven changes to the abiotic and biotic environment could alter its vulnerability to BHC. We applied a spatially explicit model of BHC growth rate potential (GRP; g g −1 d −1 ) to nine biophysical model scenarios to evaluate changes in habitat suitability in Lake Michigan. Scenarios differed in meteorology (cool, reference, warm), annual tributary phosphorus loads (0, 3300, and 5600 MTA), and the presence/absence of invasive dreissenid mussels. Mussel effects on BHC GRP relied on their contact with the surface mixed layer (SML), the depth of which was affected by meteorology. The warm year advanced the expansion of Bighead Carp habitat by increasing temperature-dependent foraging rates and lessening the time of competitive interaction with mussels due to earlier stratification separating mussels from the SML. Phosphorus loads were the most influential driver of the lake’s suitability. Compared to present conditions, we estimate BHC could have grown an additional 8–40% annually in the 1980s when mussels were not in the lake and phosphorus loads were higher. Our study demonstrates how climate change and nutrient enrichment can increase Lake Michigan’s vulnerability to BHC by affecting thermal regime and productivity, thereby limiting negative effects of dreissenid mussels on BHC growth.

Food depletion regulates the demography of invasive dreissenid mussels in a stratified lake - Alexander Y. Karatayev; Vadim A. Karatayev; Lyubov E. Burlakova; Mark D. Rowe; Knut Mehler; Mark D. Clapsadl (Limnology and Oceanography, 2018)
Lake stratification produces sharp gradients in temperature and pelagic resources which have cascading effects on the traits of aquatic populations, including invasive species and their ecosystem impacts. We study the consequences of such common environmental gradients on the demography of quagga mussels, one of the world's most aggressive invasive species. Coupling a series of in situ experiments with a biophysical model of the pelagic community, we quantify mussel growth and recruitment in littoral vs. profundal benthic habitats of eastern Lake Erie. We found that both severe food depletion and cold temperatures in the hypolimnion during summer stratification cause mussels to grow twice as slowly and currently inhibit recruitment in profundal compared to littoral habitats. Together with the high biomass and large mean mussel size found in long‐term monitoring surveys in the profundal habitats, our results imply that mussels successfully colonizing profundal habitats have relatively long lifespans with low growth rates, and therefore lower productivity, compared to mussels in shallow areas. Consequently, the bulk of dreissenid biomass in Lake Erie and other Great Lakes found in the vast but resource‐poor profundal habitats may have very limited impacts on epilimnetic communities compared to mussels in littoral areas. By contrast, mussels in profundal habitats strongly reduce food availability to hypolimnetic communities throughout the year. Thus, our results explain how the ecosystem impacts of sessile freshwater invaders are likely to vary among habitats and lakes depending on the relative size of profundal populations and the extent of stratification.

Influence of invasive quagga mussels, phosphorus loads, and climate on spatial and temporal patterns of productivity in Lake Michigan: A biophysical modeling study - Mark D. Rowe; Eric J. Anderson; Henry A. Vanderploeg; Steven A. Pothoven; Ashley K. Elgin; Jia Wang; Foad Yousef (Limnology and Oceanography, 2017)
We applied a three‐dimensional biophysical model to Lake Michigan for the years 2000, 2005, and 2010 to consider the mechanisms controlling spatial and temporal patterns of phytoplankton abundance (chlorophyll a ) and lake‐wide productivity. Model skill was assessed by comparison to satellite‐derived Chl a and field‐measured water quality variables. We evaluated model sensitivity to scenarios of varying mussel filter feeding intensity, tributary phosphorus loads, and warm vs. cool winter‐spring climate scenarios. During the winter‐spring phytoplankton bloom, spatial patterns of Chl a were controlled by variables that influenced surface mixed layer depth: deep mixing reduced net phytoplankton growth through light limitation and by exposing the full water column to mussel filter feeding. Onset of summer and winter stratification promoted higher surface Chl a initially by increasing mean light exposure and by separating the euphotic zone from mussels. During the summer stratified period, areas of relatively high Chl a were associated with coastal plumes influenced by tributary‐derived nutrients and coastal upwelling‐downwelling. While mussels influenced spatial and temporal distribution of Chl a , lake‐wide, annual mean primary production was more sensitive to phosphorus and warm/cool meteorology scenarios than to mussel filter feeding scenarios. Although Chl a and primary production declined over the quagga mussel invasion, our results suggest that increased nutrient loads would increase lake‐wide productivity even in the presence of mussels; however, altered spatial and temporal patterns of productivity caused by mussel filter feeding would likely persist.

A Lagrangian Model to Predict the Modification of Near-Surface Scalar Mixing Ratios and Air–Water Exchange Fluxes in Offshore Flow - Mark D. Rowe; Judith A. Perlinger; Christopher W. Fairall (Boundary-Layer Meteorology, 2011)

Application of the probability-based Maryland Biological Stream Survey to the state’s assessment of water quality standards - Mark T. Southerland; Jon H. Vølstad; Edward D. Weber; Ronald J. Klauda; Charles A. Poukish; Matthew C. Rowe (Environmental Monitoring and Assessment, 2009)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)